Concentration of propolis as a storage medium for avulsed teeth: a systematic review - Chhabra, Chaya; Chhabra, Kumar Gaurav; Thangeswaran, Seemadevi; Shere, Shraddha (Frontiers in Medicine, 2025)
IntroductionDental avulsion is among the most serious types of traumatic tooth injuries, involving the total displacement of the tooth from its socket within the alveolar bone. This form of injury causes detrimental effects to surrounding structures, including the periodontal ligament (PDL) & bone, cementum. Immediate transplantation of the avulsed tooth is highly advocated, as it plays a critical role in determining the success and prognosis of treatment. The primary objective of this systematic review was to assess the effectiveness of various concentrations of propolis as a storage medium for avulsed teeth, focusing on the survival capacity of PDL cells.MethodsThis literature review was carried out in accordance with the PRISMA guidelines, ensuring a transparent and systematic approach to study selection and reporting. Articles were sourced from multiple reputable databases, including Cochrane, PubMed, ScienceDirect, Scopus, Web of Science, and Google Scholar, to comprehensively identify relevant studies for inclusion. The articles were reviewed for initial reading using ZOTERO software. The methodology of the selected research studies was then assessed using the QUIN tool, which is designed to assess the quality of in vitro studies.ResultsThe initial search identified 30 articles, of which 21 underwent full-text review. Based on the predefined eligibility criteria, 11 research articles were ultimately chosen for qualitative analysis. The findings revealed that at 30 min of extraoral dry time, propolis preserved the highest number of viable periodontal ligament (PDL) cells compared to other storage media, such as HBSS, milk, coconut water, and pomegranate juice. Propolis has been studied at various concentrations, with 10% propolis showing the most promising results. It not only ensured a high number of viable PDL cells but also preserved PDL cell viability over extended periods, including 3, 6, 12, and 24 h.Conclusion10% Propolis demonstrated superior effectiveness in preserving PDL cell viability compared to other storage media. Based on these findings, propolis can be considered a preferable alternative for preserving the sustainability of PDL cells in avulsed teeth.